Monitoring skier's stress and recovery - listen to the heart - Hynynen, E. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
Almost 60 years ago Selye introduced "the general adaptation syndrome", where he investigated several internal and external stressors that may disturb the homeostatic balance. Among these stressors was, for example, strenuous exercise. The general adaptation syndrome is made up of three stages: Alarm reaction, stage of resistance, and state of exhaustion (Selye 1956).